SCIENCE IN CALIFORNIA'S ELEMENTARY SCHOOL PROGRAM. - Heffernan, Helen (Science Education, 1953)
This article examines the teaching of science in the elementary school program in California. Workshop teams have been developed to provide practical demonstration workshops in response to requests from administrators and teacher organizations. Local districts are also planning well-articulated twelve-year science programs with the help of science and education faculties of regional teacher-education institutions. Furthermore, committees on science in general education are developing science library standards, standard lists of equipment, workshops, extension courses, and Saturday field trips.